Determination of residual poly diallyldimethylammonium chloride (pDADMAC) in monoclonal antibody formulations by size exclusion chromatography and evaporative light scattering detector. (January 2019) - Khodadadian, Mehdi; Ghassemi, Maryam; Behrouz, Hossein; Maleknia, Shayan; Mahboudi, Fereidoun
Abstract: The cationic polyelectrolyte pDADMAC is widely used in biopharmaceutical industry as a flocculating agent to enhance clarification throughput and downstream filtration operations. Due to the possible toxicity, pDADMAC should be assessed for an acceptable residual level to ascertain the safety of the product to patients. The strong protein-polyelectrolyte interaction, however, can negatively affect sensitivity and accuracy of measurements. This paper reports on the application of size exclusion (SE) chromatography coupled to evaporative light scattering detector (ELSD) to the quantitative determination of pDADMAC in monoclonal antibody formulations and in process intermediates during downstream purification. The SE chromatography was performed under isocratic condition with a mobile phase consisting of 0.1% TFA in water (90%) and acetonitrile (10%) at a flow rate of 0.4 ml/min. A quantification limit (S/N = 10) of 0.85 ppm was achieved in sample matrix, which is sufficiently low for the trace analysis of this compound in protein-containing samples.